Equity in the public social healthcare protection in Tanzania: does it matter on household healthcare financing? - Felician Andrew Kitole; Robert Michael Lihawa; Eliaza Mkuna (BMC, 2023)
Abstract Efforts to promote equity in healthcare involve implementing policies and programs that address the root causes of healthcare disparities and promote equal access to care. One such program is the public social healthcare protection schemes. However, like many other developing countries, Tanzania has low health insurance coverage, hindering its efforts to achieve universal health coverage. This study examines the role of equity in public social healthcare protection and its effects on household healthcare financing in Tanzania. The study used secondary data collected from the National Bureau of Statistics' National Panel Survey 2020/21 and stratified households based on their place of residence (rural vs. urban). Moreover, the logit regression model, ordered logit, and the endogenous switching regression model were used to provide counterfactual estimates without selection bias and endogeneity problems. The results showed greater variations in social health protection across rural and urban households, increasing disparities in health outcomes between these areas. Rural residents are the most vulnerable groups. Furthermore, education, income, and direct healthcare costs significantly influence equity in healthcare financing and the ability of households to benefit from public social healthcare protection schemes. To achieve equity in healthcare in rural and urban areas, developing countries need to increase investment in health sector by reducing the cost of healthcare, which will significantly reduce household healthcare financing. Furthermore, the study recommends that social health protection is an essential strategy for improving fair access to quality healthcare by removing differences across households and promoting equality in utilizing healthcare services.